EFEKTIVITAS METODE HYPNOTEACHING DALAM PEMBELAJARAN BERBICARA BAHASA JEPANG SISWA KELAS X IPA SMA MANDALAHAYU BEKASI - Revaldi , Muhammad; Saadah Fitri Asih , Nur; Setiawati , Nia (Universitas Negeri Jakarta, 2019)
This paper is research report about the effectiveness of the Hypnoteaching method in Japanese learning speaking in class X of IPA Mandalahayu Senior High School Bekasi. Generally, there are some problems that students feel when they speaking Japanese, there are lack of confidence, lack of motivation and lack of mastery of sentence patterns and vocabulary. The role of a learning method is very important in learning process. Therefore, the author intends to use Hypnoteaching method in Japanese learning speaking in Mandalahayu Senior High School Bekasi. The purpose of this study was to determine the students ability to speak Japanese after using Hypnoteaching method, to find out the effectiveness of the Hypnoteaching method in learning to speak Japanese and to find out students responses regarding to the Hypnoteaching method. The research method used Pre-Experiment with One Group Pretest Posttest Design. The population in this research was the tenth grade students of Mandalahayu Senior High School Bekasi with 43 students of class X IPA I as the sample. The instrument of this research was pretest, posttest and questionnaire. After analyzing the data, the result of hypothesis test that t-count is higher than t-table (10,07 > 1,99) with 5% significant level. Therefore, it can be concluded that (t-count > t-table) which means that the Hypnoteaching method learning speaking in class X of IPA Mandalahayu Senior High School Bekasi. Then, the results of the questionnaire indicate that 98% students like to learning with using Hypnoteaching method, 86% students think that Hypnoteaching method can make students more confident to speaking in Japanese and 98% students think the Hypnoteaching method can increase their motivation to speaking in Japanese.